Customer application protocol for data transfer between embedded processor and microcontroller systems - Mazin R. Khalil; Laith A. Mohammed; Omar N. Yousif (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
This paper develops a new customer application protocol (CAP) to improve the efficiency of transferring data between embedded processor and microcontroller systems. The established protocol is characterized by its fidelity and simplicity for using a small header to control and monitor the data flow between the two systems. This is achieved by constructing an embedded processor system with an Ethernet intellectual property (IP) core featured by lightweight IP (lwIP) to settle a connection with a microcontroller device. The embedded system is configured on spartan6E FPGAs slice. The system performance is tested by transferring audio samples and displaying them on chipscope media. The performance test of the designed embedded system with the developed customer application protocol showed fast, efficient and high precision data exchange between the processor and microcontroller systems.